Israeli Technicians and the Post‐Colonial Racial Triangle in Papua New Guinea. Issue 3 (16th October 2015) - Cox, John
Abstract: Papua New Guinean imaginings of Israel as a potential development partner draw on Christian renderings of the Bible, but they also reflect an understanding of Israel as a modern, technologically advanced nation. As middle‐class Papua New Guineans reflect on the failures of national development since gaining independence from Australia, they express ambivalence about the appropriateness of Western models of development for the Papua New Guinean context. However, the influx of Asian investment is also seen as lacking, or even threatening; therefore, Asian models of development also fail to offer an appealing hope for the future. In this paper, I argue that these racialised understandings of modernity represent a 'post‐colonial racial triangle', a discursive field within which the moral implications of development are understood and debated. Within this triangle, Melanesians are thought to have 'culture' and (Christian) 'morality' but lack 'development'. Australians or 'whitemen' are thought to have 'development' and 'morality' but to lack 'culture'. 'Asians' are thought to have 'development' and 'culture' but to lack (Christian) morality. Taking this moral framing of race into account, Israel emerges as a possible aid donor with the credentials to reconcile these three positions as it is seen to be the possessor of 'development', 'culture', and 'morality'.